2016
DOI: 10.1186/s13014-016-0684-9
|View full text |Cite
|
Sign up to set email alerts
|

Applying a RapidPlan model trained on a technique and orientation to another: a feasibility and dosimetric evaluation

Abstract: BackgroundThe development of a dose-volume-histogram (DVH) estimation model for knowledge-based planning is very time-consuming and it could be inefficient if it was only used for similar upcoming cases as supposed. It is clinically desirable to explore and validate other potential applications for a configured model. This study tests the hypothesis that a supine volumetric modulated arc therapy (VMAT) model can optimize intensity modulated radiotherapy (IMRT) plans of other patient setup orientations.MethodsB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 20 publications
2
55
0
Order By: Relevance
“…These results echoed the superiority of knowledge‐based solution over the conventional trial‐and‐error manual planning, in line with previous publications 17, 20, 22, 23, 24, 25, 26, 27. It suggested that knowledge‐ and geometry‐based dosimetric predictions can help avoid selecting suboptimal or conflict optimization constraints as manual limitations.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…These results echoed the superiority of knowledge‐based solution over the conventional trial‐and‐error manual planning, in line with previous publications 17, 20, 22, 23, 24, 25, 26, 27. It suggested that knowledge‐ and geometry‐based dosimetric predictions can help avoid selecting suboptimal or conflict optimization constraints as manual limitations.…”
Section: Discussionsupporting
confidence: 87%
“…Model‐generated optimization objectives and priorities were assisted by additional manual constraints to make the model comply with our clinical protocols. The validations on 100+ patients have demonstrated that M 0 ‐generated personalized objectives improved plan quality and consistency significantly compared to the clinical plans 17, 20…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations